Are we sure about the evidence for zinc in prophylaxis of the common cold?. (February 2012) - Peters, Jaime L; Moreno, Santiago G; Phillips, Bob; Sutton, Alex J
Response to: Singh M, Das RR. Clinical potential of zinc in prophylaxis of the common cold. Expert Rev. Respir. Med. 5(3), 301–303 (2011).